Richard Scarry's Cars and trucks and things go. - Scarry, Richard (New York : Golden Books, 1974)
Depicts a variety of cars and other vehicles and their fun ctions.
"A Golden book."
Keywords: Automobiles -- Juvenile literature; Trucks -- Juvenile literature